2022
DOI: 10.1111/bjhp.12598
|View full text |Cite
|
Sign up to set email alerts
|

Examining drivers of self‐harm guideline implementation by general practitioners: A qualitative analysis using the theoretical domains framework

Abstract: Objectives: This study aimed to (1) examine barriers and enablers to General Practitioners' (GP) use of National Institute for Health and Care Excellence (NICE) guidelines for self-harm and (2) recommend potential intervention strategies to improve implementation of them in primary care. Design: Qualitative interview study. Methods: Twenty-one telephone interviews, semistructured around the capabilities, opportunities and motivations model of behaviour change (COM-B), were conducted with GPs in the United King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 106 publications
0
1
0
Order By: Relevance
“…Two authors undertook qualitative interview studies, analysed using the TDF framework, to identify barriers and enablers to adoption of clinical practice guidelines by HCPs, for any chronic disease [Kredo et al, 2018] and specifically for self-harm [Leather et al, 2022]. Both studies mapped findings to BCI functions using COM-B/BCW matrices, and identified multiple BCI groups of relevance for clinical practice guideline adherence (including feedback and monitoring, shaping knowledge, natural consequences, associations, repetition and substitutions, antecedents, goals and planning, and self-belief; Leather et al, 2022), stopping short of selection. Kredo et al specified a number of BCIs suitable for further evaluation including design improvements, accessibility, digital formatting, and patient engagement materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two authors undertook qualitative interview studies, analysed using the TDF framework, to identify barriers and enablers to adoption of clinical practice guidelines by HCPs, for any chronic disease [Kredo et al, 2018] and specifically for self-harm [Leather et al, 2022]. Both studies mapped findings to BCI functions using COM-B/BCW matrices, and identified multiple BCI groups of relevance for clinical practice guideline adherence (including feedback and monitoring, shaping knowledge, natural consequences, associations, repetition and substitutions, antecedents, goals and planning, and self-belief; Leather et al, 2022), stopping short of selection. Kredo et al specified a number of BCIs suitable for further evaluation including design improvements, accessibility, digital formatting, and patient engagement materials.…”
Section: Resultsmentioning
confidence: 99%
“…(2) Implementation of diagnostic guidelines Two authors undertook qualitative interview studies, analysed using the TDF framework, to identify barriers and enablers to adoption of clinical practice guidelines by HCPs, for any chronic disease [Kredo et al, 2018] and specifically for self-harm [Leather et al, 2022]. Both studies mapped findings to BCI functions using COM-B/BCW matrices, and identified multiple BCI groups of relevance for clinical practice guideline adherence (including feedback and monitoring, shaping knowledge, natural consequences, associations, repetition and substitutions, antecedents, goals and planning, and self-belief; Leather et al, 2022) A subsequent effectiveness study by the same group [Porcheret et al, 2018] described an uncontrolled trial of the final workshop, with GP competency measured through review of a video-recorded simulated consultation, before and after the intervention; competency score increased significantly at two time points, one month (p=0.001) and five months (p=0.001) after the workshop.…”
Section: Narrative Synthesismentioning
confidence: 99%
“…RE-AIM and NASSS informed the data collection plan, to capture a comprehensive set of individual-and system-level factors (Table 1 [49,50,53,54]). The COM-B model was used to analyse how various factors influenced engagement and behaviour [55][56][57][58][59]. The SRQR [60] (S1 Table ) and TREND [61] checklists (S2 Table ) were used to ensure completeness of reporting.…”
Section: Methodsmentioning
confidence: 99%